2008
DOI: 10.1016/j.psyneuen.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Whites have a more robust hypothalamic–pituitary–adrenal axis response to a psychological stressor than blacks

Abstract: SummaryObjective-Differences in the hypothalamic-pituitary-adrenal (HPA) axis response to stress may confer differences in susceptibility to a variety of diseases. We hypothesized that whites would differ from blacks in HPA axis response to a psychological stressor.Design-Healthy subjects aged 18-30 were recruited from Baltimore, Maryland. At initial assessment, they completed psychometric tests measuring anxiety, mood, and personality. Subjects then participated in the Trier Social Stress Test (TSST), which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 37 publications
(47 reference statements)
3
45
0
Order By: Relevance
“…The GA/GG allele women exhibited nonsignificantly higher basal cortisol values during the stress protocol, possibly attenuating the stress response due to a ceiling effect or negative feedback dampening of HPA reactivity. An elevated baseline is not a persistent characteristic of the GA/GG allele genotype; the female genotype groups exhibited no baseline differences during the placebo condition in the naltrexone protocol (Figure 2), as also found by others (Chong et al, 2008). Another group reported elevated cortisol secretion in AA women (Bart et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…The GA/GG allele women exhibited nonsignificantly higher basal cortisol values during the stress protocol, possibly attenuating the stress response due to a ceiling effect or negative feedback dampening of HPA reactivity. An elevated baseline is not a persistent characteristic of the GA/GG allele genotype; the female genotype groups exhibited no baseline differences during the placebo condition in the naltrexone protocol (Figure 2), as also found by others (Chong et al, 2008). Another group reported elevated cortisol secretion in AA women (Bart et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…The present outcomes supported by some (12,32,46,53,62,81), but not other (18,48,55,70), indirect analyses. Contradictory earlier data may reflect in part the influence of stressor type on sex differences (71); small numbers of subjects studied (40,59,77,78); morning vs. late-day sampling (72); and possible effects of ethnicity (14,80).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other studies have reported no age or sex effects (19,29,32,46,48,53). Certain of these discrepancies could be due to ethnicity differences (14,80), time-of-day effects (72), measurement of cortisol in plasma, saliva, or urine (41,43,58), nature of stressor (54,71), basal vs. stressed states (2,81), concurrent obesity (1,23,33,67,68,70), estrogen use (46), stage of menstrual cycle (40), dietary carbohydrate intake (65), and potential sex-by-age interactions (78). The last consideration has been assessed in untreated children (28) and in adults following sequential dexamethasone/CRH exposure (30).…”
mentioning
confidence: 92%
“…For instance, lower cortisol levels upon waking and during the day (after controlling for socioeconomic and psychological factors) have been found in African Americans compared with Whites (Bennett et al, 2004;Cohen et al, 2006). In addition, African Americans reportedly have a lower HPA axis response to psychological stress compared with Whites (Chong et al, 2008). The ethnic variations in adrenocortical response to the stress during laboratory procedures may also be explained by the differences in BMI observed in Indo-T and Afro-T (Afro-T had higher BMI than Indo-T).…”
Section: Response To Alcohol In Indo-t and Afro-tmentioning
confidence: 98%